Knowledge, attitude, and practice of medical students regarding immunization and National Maternal and Child Health program in India - Singh, Lily; Saxena, Pranjali; Faridi MMA (Asian Journal of Medical Sciences, 2022)
Background: There are gaps in knowledge, attitude, and practice (KAP) regarding immunization and National Maternal and Child Health program among health care workers. Aims and Objectives: This study aims to study the KAP gaps related with immunization among medical students at a teaching institute. Materials and Methods: A total of 321 medical students were evaluated using a 54-item pre-validated inventory containing 36 items on knowledge, 8 on attitude, and 10 on practice with total possible scores of 55, 8, and 17, respectively. Details regarding type of student (undergraduates, intern, and postgraduates), sex, age, and marital status were noted. For illustrative purposes, the domain scores were transformed to percentages. Data were analyzed using SPSS 21.0 Software. Kruskal–Wallis, Mann–Whitney U tests, and Pearson correlation coefficient were employed for statistical analysis. Results: Maximum were final year MBBS (n=146) followed by interns (n=106) and 1st year postgraduate students (n=69). Majority were female (55.8%), aged 22–25 years (74.8%), and unmarried (91.9%). Mean percentage scores for knowledge and attitude were 51.44±13.35% and 65.54±31.05%. For immunization subdomain of knowledge, attitude, and practice, these were 58.45±16.15%, 72.20±32.59%, and 36.74±13.10%, respectively. Knowledge and practice scores showed a significant association with type of student. Attitude scores did not show a significant association with demographic profile of student. Maximum scores for all the domains were observed among postgraduates. Overall practice scores were much lower than knowledge and attitude. A significant correlation was observed between knowledge, attitude, and practice scores. Conclusion: The study identifies wide gaps in KAP of medical students that indicate need for strategic interventions.